Desiminasi Lesson Study Sebagai Wahana Pemberdayaan TPQ Assalami Dusun Mojoseto Desa Mojoseto Kecamatan Gondang Kabupaten Nganjuk - Mustofa, Idam; Kholik, Husnul; Ristianah, Niken; Huda, Afiful; Muda’i, Syaiful (LP3M STAI Darussalam Krempyang Nganjuk, 2019)
Educational problems require all parties to constantly innovate. The effort that can be done is the adoption of educational models through diffusion or dissemination to help educational institutions solve their problems well. TPQ Assalami Mojoseto Gondang Nganjuk as an assisted partner still applies learning that is classified as traditional, especially in the ‘ubudiyah lesson. However, the management is very eager to improve the quality of learning by adding subject matter. The solution given is the dissemination of teaching ‘ubudiyah lesson. This community development combines the Lesson Study and Asset-based-Community Development (ABCD) methods. The implementation of community service consists of: 1) Workshop and dissemination of the development of innovative creative teaching materials; 2) Assistance in developing innovative creative teaching materials through lesson study; 3) Reflections on the results of training and assistance in developing innovative creative teaching materials; and 4) Assistance in involving community participation. Dissemination of lesson study to develop teaching of ‘ubudiyah is not only in curriculum development by mere educators, but can also strengthen the capacity of managers to invite community participation in education.